A mixed method study of the factors influencing the validity of medical and medication histories obtained from potential healthy adult clinical trial participants - Ltayef, Hanan (Department of Medicine, 2020)
Background: The medical histories of patients are data picked up by a doctor by making inquiries of the patient and of other individuals who know the individual and can give a reasonable response. In clinical trials, obtaining an accurate medical and treatment history is also an important factor in establishing whether or not a person is an eligible participant, and thereafter supports the assessment of any change in health during the trial, for example, the assessment of adverse events (AEs). Study objectives: To understand discrepancies between the medical histories from online self-reports, electronic medical records, and in-depth interviews of those applying to be part of an adult volunteer database for clinical trials; explore ways of engaging with potential volunteers, such that self-reported medical histories are as comprehensive as possible; explore the feasibility of accessing electronic records for those responding to advertisements. Methodology: This study was designed as mixed methods, with sequential explanatory design collecting quantitative and qualitative data and nested in an existing adult volunteer database. people from the Cape Town community were invited to join the database, in response to an advertisement and through a link to the database website; particularly those who were potentially eligible for a typical healthy volunteer trial, and who reported different information to that obtained from the electronic records. Results: 38 people responded to the online questionnaire, the majority being female. According to the online self-report questionnaire, ten people (10/38; 26.3%) had chronic medical conditions; mostly HIV (7/10; 70%). We accessed the Western Cape electronic medical records for only 8/38 (21%). Comparing the online questionnaire with the medical records, it was found that 25% of respondents had no difference in information. 10/38 people (26.3%) agreed to participate and were available for an in-depth interview. The main findings were: 1) a very low response rate to the advertisement, 2) people in this community are willing to consider taking part in clinical research, but have different understandings of what that means, 3) there were discrepancies between online self-reported health and medication data and what was found in a pilot database of electronic public health records and during a face-to-face interview, 4) the reason for these differences, as perceived by participants, included forgetting some information, feeling it was not relevant or important to report because of the attributes of the online questionnaire and 5) these participants had no concerns about us accessing their electronic medical records. Conclusion: Our study provides some evidence for optimal places to advertise for an adult volunteer database, and the appropriate wording and format of both the advertisements and the online questionnaire. More efforts are needed to educate the general public on understand the meaning of clinical trials. Electronic medical records may be accessed to help understand potential participants’ eligibility for trials, but the feasibility of accessing such data timeously may need further negotiation.